An introduction to food systems thinking: How members of multi-stakeholder platforms in Vietnam can apply food systems thinking in practice - Pittore, Katherine; Hai, Tran (Wageningen Centre for Development Innovation, 2021)
Over the last five years Wageningen Centre for Development Innovation has been exploring the role that Multi-Stakeholder Platforms (MSPs) can play in supporting countries in food system transitions which places healthy diets at the centre, as part of the Platforms for Healthier Diets project. This work was carried out as part of the Flagship on Food Systems for Healthier Diets (FS4HD) is one of the programs of the IFPRI-led CGIAR Agriculture for Nutrition and Health (A4NH) project. The project focuses on four countries: Bangladesh, Ethiopia, Nigeria and Vietnam. The platforms for Healthier Diets project began with conceptualizing the idea of multi-stakeholder platforms, as well as healthier diets, and identification of a set of criteria that could be used to map multi-stakeholder platforms in the four A4NH countries. This work was followed by a desk based mapping of all the platforms that met the criteria for multi stakeholder platforms working healthier diets (broadly defined). The results of this mapping were shared with stakeholders in Vietnam, Nigeria, and Bangladesh, who reflected on the research findings. Finally, we explored how we could support countries to embed and scale ideas of healthy diets as a central goal of the food system, by considering the key policy priorities of each country and how platforms engage with these policies, for example by supporting with agenda setting or policy implementation. We found that in many countries, policies are looking more holistically at the food system compared to MSPs which tend to have a narrow focus, for example looking at the urgency around tackling high levels of malnutrition or scaling up specific types of agricultural interventions. At the time the scans were carried out, we did not find any multi-stakeholder platforms in the four A4NH countries that are working on food systems explicitly. However, while this is not currently happening, we believe MSPs may hold real potential for supporting effective food systems governance, and the transition to food systems which support healthy diets for all citizens. Herens et al. (forthcoming) suggested MSPs could support food systems transformations, but the ability of MSPs to span boundaries between food systems actors needs to be strengthened, including by building capacity at the individual, institutional or organizational level. The training on food systems held in Vietnam was an initial start to supporting the improved capacity of MSPs to support a food Systems based framing, and to pilot potential tools to increase food system knowledge, that can be used with other MSPs in other context. In the past few years, more and more materials have come available to support platforms, organizations and individuals to better incorporate food systems thinking in their work. However, as many of these tools are quite new, there has been less opportunity to pilot then with practitioners, and adjust to make them more user friendly. This report is structured in two parts. The first part presents key findings from a two day online training “An Introduction to Food Systems Thinking: How Members of Multi-Stakeholder Platforms in Vietnam Can Apply Food Systems Thinking in Practice”. The second section presents an overall reflection on the food systems decision support tool and suggestions for how this tool could be further strengthened.